Dinamika Populasi Kepiting Bakau (Scylla sp.) di Perairan Kabupaten Sinjai - Ridha Alamsyah; A. Liswahyuni; Mapparimeng Mapparimeng; Armita Permatasari (Biogenesis: Jurnal Ilmiah Biologi, 2017)
Mangrove crab catching activity to increase and tends to lead exploitation pressure. This study aims to determine the rate of growth, mortality, and rate of exploitation. Sampling on fishermen and collectors whose fishing locations are in predetermined areas. Measurements taken are using ruler and caliper 0,05 for carapace width. Sample measurements were carried out to obtain information on the dynamics of the mangrove crab population. The results obtained are: length of carapace minimum (Lmin) 61 mm, maximum (Lmax) 173 mm, Asimtot carapace width (L∞) 177,7 mm with growth coefficient (K) 0,1 per year, and the value t0 obtained -0,2907. Total mortality rate (Z) 0,743 per year, natural mortality (M) 0,177 per year and mortality of capture (F) 0,566 per year. The rate of exploitation (E) 0,762 per year, indicating that there has been over exploitation of mangrove crabs in Sinjai District.